Odcienie dekadencji we współczesnej nowoczesności a dylematy reprezentantów nauk społecznych - Radziewicz-Winnicki, Andrzej; Walancik, Marek (Studia Edukacyjne, 2017)
This paper attempts to explore the processes involved in the methodological, intellectual and cultural reproduction (valorization) of the traditional status of social sciences in the beginning of the 21st century, with specific references to commercial conditions. Compensation and reproduction is discussed as a study of universities experience in the period of numerous changes. Particularly the economic and cultural determinants of selected problems and the direction of the transformation which is still in the course in the Polish democratic and the normative order in the post-totalitarian society is criticized not only by the author, but also university professors, lectures and students. However, in the end of paper, the author shows optimism connected with the reproduction of the expected reforms in higher education in Poland and in the post-industrial world.